Rethinking independent cinema: Public funding, market oligopoly and the film industry in Turkey - Akkaya, Ercan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
In the Turkish film industry, the term independent is mostly used for certain kinds of film to differentiate between mainstream films. Even though the terms independent and mainstream are used to refer to films’ positions within the field according to their political, hegemonic, artistic and material conditions, this thesis seeks to identify the economic background of the distinction of these two terms. Misframed public funding mechanisms and a strengthening market oligopoly in distribution and exhibition markets show that independence needs rethinking in economic terms. The Turkish film market shows that there are two factors that need to be included in the debate on independent film due to the fact that 1) public funding mechanisms and legal regulations have a definitive effect on the way the sector works on a day to day basis; 2) the present market oligopoly in distribution and exhibition market underlines the importance of distribution and exhibition of a film’s lifecycle as much as production. Even though the term independent film has been in circulation for a long while, the economic conditions of these films are missing in the general debate.
Keywords: Motion picture industry -- Turkey.; Independent films -- Turkey.